KINERJA KARYAWAN DI KANTOR SABLON JEJAK7KAOS CELEBES SCREEN PRINTING KOTA MAKASSAR - Isyam, Isyam; Malik, Ihyani; Syarif, Ahmad (Universitas Muhammadiyah Makassar, 2023)
This study aimed to find out how the performance of employees at Jejak7kaos Celebes Screen Printing Office in the City of Makassar. This study used a qualitative research methods and the type of research used descriptive. Data collection techniques were observation and interviews. The results showed four quality indicators, namely by looking at the discipline of employees, discipline at work (coming on time, doing the job properly and correctly) and utilization of facilities (use of tools). printing equipment properly and correctly). Quantity, to improve employee performance in need of a motivation. Motivation could be seen form of additional salaries, vacations, and other gifts that could increase the ability and willingness of employees to work. Punctuality, on time to come to the office and on time in finishing his work. Effectiveness, the ability to use the raw materials used, for example the use of computers, printers, and other printing equipment.